The effects of myofascial release technique for patients with low back pain: A systematic review and meta-analysis. (June 2021) - Chen, Ziyan; Wu, Jinlong; Wang, Xiaodong; Wu, Jieqing; Ren, Zhanbing
Highlights: Myofascial Release Technique has significant effects on reducing back disability in patients with low back pain. MFR can improve the effect of physical therapy alone and exercise therapy alone, and that MFR can be an effective adjuvant therapy. Abstract: Objective: The purpose of this meta-analytic review was to quantitatively examine the effects of myofascial release technique (MFR) on pain intensity, back disability, lumbar range of motion, and quality of life in patients with low back pain (LBP). Methods: Potential articles were retrieved using five electronic databases (Web of Science, PubMed, Scopus, China National Knowledge Infrastructure, and Wanfang). The search period was from inception to January 27, 2021. Two researchers independently completed record retrieval and selection, data extraction, and methodological quality assessment. Randomized controlled trials (RCTs) assessing the effect of MFR on pain intensity, back disability, lumbar range of motion, and quality of life in LBP patients were included. Pooled effect sizes were calculated using random effects models and 95 % confidence interval (95 % CI). Results: Data from eight RCTs (386 patients with back pain) meeting the inclusion criteria were extracted for meta-analysis with methodological quality assessment scores ranging from 6 to 10. Compared to the control intervention, MFR induced significant decrease in back disability (SMD = −0.35, 95 % confidence interval [CI] = −0.68, –0.02, P = 0.04, I ² = 46 %, n = 284). MFR induced non-significant decrease in the pain intensity (SMD = −0.12, 95 % confidence interval[CI] = −0.35, 0.11, P = 0.32, I ² = 0%, n = 294), non-significant improvement in quality of life (SMD = −0.09, 95 % confidence interval [CI] = −0.46, 0.28, P = 0.62, I ² = 0%, n = 114), and non-significant improvement in lumbar range of motion (Flexion SMD = 0.57, 95 % confidence interval [CI] = −0.09, 1.24, P = 0.09, I ² = 54 %, n = 80) (Extension SMD = 0.68, 95 % confidence interval[CI] = −0.72, 2.08, P = 0.34, I ² = 89 %, n = 80) (Right flexion SMD = 0.05, 95 % confidence interval[CI] = −0.90, 0.99, P = 0.92, I ² = 78 %, n = 80) (Left flexion SMD = 0.14, 95 % confidence interval[CI] = −0.59, 0.88, P = 0.70, I ² = 64 %, n = 80). Conclusion: The findings suggest that MFR can improve the effect of physical therapy alone and exercise therapy alone, and that MFR can be an effective adjuvant therapy. Meta-analysis showed that MFR has a significant effect on reducing back disability in patients with low back pain, but no significant effect on reducing pain intensity, improving quality of life, and improving lumbar range of motion.